Surface-Modification Hyperbranched Polyaminoester Connected to Fused-Silica Capillary Microchips for Protein UV Analysis - Liu, Bing; Yang, Wen; Xu, Lin; Scott Edgar, J.; Shou, Chongqi (Asian Journal of Chemistry, 2013)
A “double-T” poly(dimethyl siloxane) microfluidic chips with 50 μm separation channel and 200 μm fabricated by the shooting technique. 10 cm fused-silica capillary was connected with the microfluidic chip through the tail end of the microchannel. With this method the dead volume which resulted from the connecting could be reduced effectively. Hyperbranched polyaminoesters with multiple hydroxy groups and perfect hydrophilic were synthesized by one-step technique. Then, chips were modified by hyperbranched polyaminoesters, which were treated in oxygen atmosphere in advance. The surface of poly(dimethyl siloxane) after modification was characterized using atomic force microscopy and scanning electron microscope.Through these methods the contact angles of poly(dimethyl siloxane) were lowered, that could inhibit the protein adsorption and electroosmotic flow of microchannel effectively. 2 mg/mL Adenosine and L-tryptophan were detected and separated by UV analysis. This study provides a new and rapid method of protein microfluidic chip modification.